Proteomic Analysis of Humoral Immune Components in Bronchoalveolar Lavage of Patients Infected or Colonized by Aspergillus fumigatus - Dellière, Sarah; Duchateau, Magalie; Wong, Sarah Sze Wah; Giai Gianetto, Quentin; Guegan, Hélène; Matondo, Mariette; Gangneux, Jean-Pierre; Aimanianda, Vishukumar (Frontiers in Immunology, 2021)
Humoral immune components have been individually studied in the context of interaction of host with Aspergillus fumigatus, a major airborne fungal pathogen. However, a global view of the multitude and complex nature of humoral immune components is needed to bring new insight into host-Aspergillus interaction. Therefore, we undertook comparative proteomic analysis of the bronchoalveolar lavage fluid collected from the individuals infected or colonized with A. fumigatus versus controls, to identify those alveolar humoral components affected upon A. fumigatus infection. Complement proteins C1q, C8 beta-chain, factor-H, ficolin-1, ficolin-2, mannan binding lectin serine peptidase 2, pentraxin-3 and the surfactant protein-D were identified as the major humoral immune components affected by A. fumigatus infection and colonization. Based on this observation, we hypothesize that crosstalk between these humoral components is essential during host-Aspergillus interaction giving new specific leads to study for better understanding the pathogenesis. Furthermore, the affected humoral components could be potential diagnostic markers of A. fumigatus infection or colonization.